What drives consumer demand for packaged rice? Evidence from South and Southeast Asia - Bairagi, Subir; Gustafson, Christopher R.; Custodio, Marie Claire; Ynion, Jhoanne; Demont, Matty (Elsevier, 2021)
The demand for improved packaging and labeling of rice is expected to rise in Asia due to rapid income growth, growing food safety concerns, and retail market transformation. Currently, about half of the rice in urban markets in South and Southeast Asia is sold in packaged form. However, urban market shares of packaged rice are highly heterogeneous among countries and range from 11% in the Philippines to 18% in Vietnam, 45% in India, 51% in Indonesia, 58% in Cambodia, 63% in Bangladesh, and up to 64% in Thailand. We identify the drivers of consumer demand for packaged rice by fitting a probit model on survey data from more than 4000 urban and rural consumers from seven countries in South and Southeast Asia. The results indicate that demand for packaged rice is driven by income, education, employment, household size, intrinsic quality attributes such as rice fragrance, per capita rice consumption and purchase frequency. The drivers of demand are found to depend on the stage of retail market transformation, distinguishing Thailand as a market leader from the rest of the countries in South and Southeast Asia. The findings in this study can help policymakers learn from more advanced countries and rice sectors in South and Southeast Asia and develop country-specific strategies to foster modernization and inclusiveness of rice retail markets consistent with their sectors’ state of progress in retail transformation.